Komunikasi Virtual pada Komunitas Growth Space di Media Sosial Discord - Rahayu, Putri Puspita; Sukendro, Gregorius Genep (Prologia, 2024)
This study aims to examine the patterns and processes of virtual communication within the Growth Space community that take place on Discord social media and understand the supporting and inhibiting factors in implementing the Growth Space community's virtual communication patterns that take place on Discord social media. The research was conducted using netnography methods with a qualitative descriptive approach. Researchers to obtain the data from interviews and observations. The results of the study show that the virtual communication pattern that occurs in the Growth Space Community is included in the pattern type of all channels. Communication patterns include question-and-answer activities, discussions around certain topics, event sessions (outpouring) related to certain topics via text or voice calls, as well as the existence of rules and imposing sanctions on members who violate them. Supporting factors for virtual communication in the Growth Space Community are active members, supportive moderators who recognize the target audience in conveying information, interesting and varied topics, diverse and flexible media for delivering messages, free access to information, and a feeling of security in exchanging information. While the inhibiting factors include technical constraints, missed communication, and out-of-topic. Penelitian ini bertujuan untuk mengkaji pola dan proses komunikasi virtual komunitas Growth Space yang berlangsung di media sosial Discord dan memahami faktor-faktor pendukung dan penghambat dalam penerapan pola komunikasi virtual pada komunitas Growth Space yang berlangsung di media sosial Discord. Penelitian dilakukan menggunakan metode netnografi dengan pendekatan kualitatif, peneliti untuk mendapatkan datanya akan melakukan interview atau wawancara dan observasi. Hasil penelitian menunjukkan bahwa pola komunikasi virtual yang terjadi dalam Komunitas Growth Space termasuk dalam jenis pola semua saluran. Pola komunikasi termasuk aktivitas tanya jawab, diskusi seputar topik tertentu, sesi curhat (curahan hati) terkait topik tertentu melalui text maupun voice call, serta adanya aturan dan memberikan sanksi kepada anggota yang melanggar. Faktor pendukung komunikasi virtual dalam Komunitas Growth Space adalah anggota yang aktif, moderator yang supportive dan mengenali sasaran khalayak dalam menyampaikan informasi, topik yang menarik dan beragam, media penyampaian pesan yang beragam dan fleksibel, akses informasi yang bebas, dan perasaan aman dalam bertukar informasi. Sedangkan faktor penghambatnya diantaranya yakni kendala teknis, missed-communication dan out of topic.